Participatory urbanism: creative interventions for sustainable development - Poljak Istenič, Saša (Acta geographica Slovenica, 2019)
The paper presents the concept of participatory urbanism and analyses its practical implications in the context of the City of Ljubljana. It assesses the potential of participatory methodology for physical and social interventions in public spaces through the case-studies of two creative spatial practices: urban community garden Onkraj gradbišča / Beyond the construction site and community-led renovation of Savsko naselje neighbourhood. It indicates how bottom-up initiatives can contribute to sustainable development of an urban area, especially to its environmental and social features. It concludes with the ideas of how cities might engage with bottom-up spatial practices to increase the effectiveness of urban spatial planning, management and administration, and to boost their green creative image.